Effect of drying and rewetting of the crown fragments prior to reattachment in tooth fragmented - Shirani F.; Malekipor MR.; Aghaei F. (Tehran University of Medical Sciences, 2008)
"nBackground and Aim: Fractured anterior teeth can be restored by adhesive bonding of the separated fragment to the remaining tooth structure. This invitro study evaluated the force required for fracture of rebonded fragments which were dried and rewetted for various time intervals prior to bonding. "nMaterials and Methods: One hundred and eight human mandibular incisors were selected and were divided into 9 groups and then were fractured. The fragments were stored in air at room temperature and ambient humidity. They were air dried for 30 minutes in group 1, 2 and 3,  6 h in group 4 and 5,  24 h in group 6 and 7, and 3 days in groups 8 and 9. The apical parts of the fractured teeth were stored in water.After storage in air, each fragment in group 1 was bonded to the remaining apical tooth structure with a bonding agent and flowable composite.In groups 2, 4, 6 and 8 after air drying the fragments were stored in water for 30min. The time of storage in water in groups 3, 5, 7, 9 was 24 hours. Then each fragment was bonded to the apical part structure. The mean force required for fracture was measured by a mechanical testing machine. One way ANOVA and Tuckey tests were used for analysis. "nResults: There were statistically significant differences between different groups (p<0.001).The highest and lowest force required for fracture belonged to groups 3 and 8 respectively. The force required for fracture in group 1 was lower than group 2, 3, 5 and 7 and 9 and more than groups 4,6 and 8 with significant differences.While there were no significant differences among groups 3, 5, 7, 9 and 4, 6, 8 the force required for fracture in groups 2, 3, 5, 7 and 9 was more than 4, 6, 8 with significant differences. "nConclusion: This research revealed that the force required for fracture was affected by air storage of fragments prior to bonding. Also showed that with an increase in duration of drying the force required for fracture decreased and after a period of time it becomes steady. This study showed that in order to increase the fracture strength after air drying the fragment should be immersed in water for at least 24 hours prior to bonding.